Normative and Sociological Review of the Selangor Majlis Fatwa Decree on Dowry - Bin Ramli, Muhammad Afiq Najmi; Misran; Achyar, Gamal (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2025)
The determination of the minimum level of dowry issued by Majlis Fatwa should contain elements of benefit for both the husband and the wife. The determination of the level of dowry is considered with various aspects such as customs and maslahat for the people in the State of Selangor. This study aims to find out the provisions of the minimum level of dowry in Islamic law, the legal basis of Majlis Fatwa State of Selangor in determining the minimum level of dowry of RM 300 and the relevance of Majlis Fatwa State of Selangor in determining the minimum level of dowry of RM 300 to the community. This research is field research located in Selangor. The data sources used by the author are primary data sources, namely data obtained directly from interviews and secondary data sources obtained from various documents related to this research. The results showed that the provision of the minimum level of dowry in Islamic law is not specifically determined about the level of dowry for marriage. Islam only orders to lighten the dowry and facilitate marriage. The legal basis of Majlis Fatwa State of Selangor in determining the minimum level of dowry of RM 300, based on the hadith from Aisha, from the Prophet SAW, who said: (The women whose blessings are great are the women who facilitate the financing of their marriages). This hadith is seen as still not fulfilling the main purpose and objective for the people living today, because the people of the State of Selangor still feel the burden of financing marriage. This also protects the right of dowry so that the determination of the dowry rate does not apply arbitrarily and complicate marriage. The relevance of Majlis Fatwa State of Selangor in determining the minimum level of dowry of RM 300 to the community is still not appropriate, because what is set only the minimum limit. Majlis Fatwa should also determine the maximum level which will be good between the man and the woman.